Does Extreme Leukocytosis Predict Serious Bacterial Infections in Infants in the Post-Pneumococcal Vaccine Era? The Experience of a Large, Tertiary Care Pediatric Hospital. Issue 6 (June 2015) - Danino, Dana; Rimon, Ayelet; Scolnik, Dennis; Grisaru-Soen, Galia; Glatstein, Miguel
<x xml:space="preserve">Abstract</x> Background Extreme leukocytosis, defined as a peripheral white blood cell count greater than 25, 000/mm3, may alarm clinicians and prompt extensive evaluation in infants with fever, especially in the pediatric emergency department. Methods We reviewed data from children aged 3 to 36 months with extreme leukocytosis, fever and the risk of serious bacterial infections (SBI) at our institution from July 2010 to December 2012, a period after the universal introduction of pneumococcal vaccine. Results Serious bacterial infection was recorded in 57 (39%) of the 147 infants. The most common SBI were segmental or lobar pneumonia, in 28 (19%) patients, and urinary tract infection in 16 (10.9%) patients. Three patients had positive blood cultures, corresponding to a bacteremia rate of 2%. C-reactive protein was significantly higher in the SBI group than in the non-SBI group. Conclusions All well-looking febrile infants with white blood cell greater than 25, 000/mm3 should undergo a chest radiograph unless there are clear physical findings that indicate a different etiology. Urine culture should be considered in women. C-reactive protein can have an added value in the differential diagnosis.